Dyskurs edukacyjny a rozwój interkulturowej kompetencji negocjacyjnej podczas lekcji języka obcego na przykładzie języka hiszpańskiego - Spychała, Małgorzata (Neofilolog, 2019)
Nowadays young people need not only specific knowledge, but also a wide array of skills, including language skills, enabling them to better adjust to intercultural realities. One such skill is negotiation, coupled with the selection of an appropriate type of discourse. The aim of the present paper is to analyze the features, forms and styles of educational discourse that support the growth of intercultural negotiation competence in foreign language classes. Particular attention will be given to the structure of the content of discourse: intercultural communication and negotiation. The author seeks to answer the question whether students should aim at using multi-discursive competence in order to effectively talk to or negotiate with representatives of other cultures. The analysis of specialized discourse allows her to find out whether or not teaching business language in foreign language classes is a sine qua non condition for mastering intercultural negotiation competence. The paper also aims to determine in a precise manner the competences of a student as an intercultural negotiator and mediator. Therefore, it presents general principles and examples of communication (discourse) practices that may contribute to the development of intercultural negotiation and mediation competence under classroom conditions. The last section contains an overview of selected handbooks for learning Spanish from the perspective of developing intercultural negotiation competence, with a focus on the presence of elements that can be used for this purpose.